1978
DOI: 10.2113/gsecongeo.73.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Magmatic vapor plumes and ground-water interaction in porphyry copper emplacement

Abstract: Porphyry copper deposits, all showing similar geological characteristics, occur in Tertiary and older orogenic-volcanic belts around the w•orld. Recent isotope and fluidinclusion studies have shown that in a number of deposits the development of the characteristic ore alteration pattern, at some stage, involved the interaction of meteoric ground waters with saline fluids evolved from a magma. A fluid dynamic model is proposed for porphyry copper emplacement which focuses on the interaction of a buoyant low-sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
156
0
1

Year Published

1980
1980
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 350 publications
(163 citation statements)
references
References 30 publications
6
156
0
1
Order By: Relevance
“…It is also commonly assumed that if a vapour phase exsolves at ail, it is a low density fluid, but at typical porphyry conditions (i.e., 600-700°C and 500-1000 bars), vapour has a relatively high density. An additional misconception is that the mass of the exsolving vapour is much smaller than that of the co-evolved liquid phase (Burnham, 1979), and is thus of little importance in metal transport, but a model proposed by Henley and McNabb (1978) demonstrated that the mass of an exsolving magmatic plume is vapour-dominated. Thus, several of the underlying assumptions for liquid-dominated metal transport are unfounded, and so the vapour phase should be more seriously considered as a transport agent in oreforming processes.…”
Section: The Vapour Transport Of Metalsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also commonly assumed that if a vapour phase exsolves at ail, it is a low density fluid, but at typical porphyry conditions (i.e., 600-700°C and 500-1000 bars), vapour has a relatively high density. An additional misconception is that the mass of the exsolving vapour is much smaller than that of the co-evolved liquid phase (Burnham, 1979), and is thus of little importance in metal transport, but a model proposed by Henley and McNabb (1978) demonstrated that the mass of an exsolving magmatic plume is vapour-dominated. Thus, several of the underlying assumptions for liquid-dominated metal transport are unfounded, and so the vapour phase should be more seriously considered as a transport agent in oreforming processes.…”
Section: The Vapour Transport Of Metalsmentioning
confidence: 99%
“…The high Mo solubility at low temperature observed in the present study indicates that the vapour phase may play a much more important role in the transport of Mo in natural systems than previously thought. For example, as the vapour phase is thought to dominate porphyry-forming systems (Henley and McNabb, 1978), vapour transport may be an important process in the formation of economic Mo porphyry deposits.…”
Section: Geological Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…At these depths the saline geothermal fluids are distributed over the base of the whole convection system. Henley and McNabb [1978] argue that a phase separation occurs in brines at high temperatures, resulting in the formation of a boundary layer of highly concentrated brine between the convective plumes and hightemperature rock. Thus the interface region will be characterized by low resistivity.…”
Section: Deep Structure In the Tvzmentioning
confidence: 99%
“…One apparent effect of the convecting ground water on the venting fluid is the dispersion of heat and salinity by fluid mixing at the edges of the venting plume (Henley and McNabb, 1978). This effect may be stronger in the central part of a concave intrusion environment, where the flow direction of the convecting ground water is just opposite to that of the venting fluid.…”
Section: Forced Venting Vs Convective Fluid Flowmentioning
confidence: 99%